Comparative Study of QoS on Video Meeting Tool Application in 4G LTE Network using Wireshark - Sirmayanti Sirmayanti; Asriani Tain; Nurul Khaerani Hamzidah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Video meeting is a broadband internet-based service for long-distance communication, both visual and audio, in one room or in different rooms at the same time. Network testing using wireshark software connects to the Telkomsel operator's 4G LTE network. QoS parameters can display network quality such as throughput, packet loss, delay and jitter. The research experiment test used two conditions with different variables in the five types of video meeting tools being compared; zoho meeting, cisco webex meeting, google meet, zoom meeting and microsoft teams. First-condition uses random variables that do not consider the value of the number of participants and camera & microphone conditions to each client. Second-condition uses a fixed variable that the number of each client is 5 participants for each application (camera & microphone is on). The first-condition results showed that only Zoom Meeting which had a QoS value classified as Poor (index 1), especially the jitter value, compared to other applications. This application has an average jitter of 151,871 ms, that compared to TIPHON standard of 125 ms to 255 ms. The second-condition obtained Very Good QoS on throughput, packet loss and delay variables in all applications. Their variable jitter in each application is Zoho Meeting (0.101 ms), Cisco Webex meeting (0.074 ms), Google Meet (0.179 ms), Zoom meeting (0.021 ms), and Microsoft Teams (0.015 ms) which only in the standard 0 ms to/ d 75 ms. However, all applications according to the TIPHON standards are still in the Good category (index 3). The overall index average of all applications shows Good QoS.Keywords: video meeting, wireshark, quality of service, 4G LTE.